Crizotinib in ALK+ inflammatory myofibroblastic tumors—Current experience and future perspectives. Issue 4 (29th December 2017) - Theilen, Till‐Martin; Soerensen, Jan; Bochennek, Konrad; Becker, Martina; Schwabe, Dirk; Rolle, Udo; Klingebiel, Thomas; Lehrnbecher, Thomas
Abstract: Inflammatory myofibroblastic tumor (IMT) and its subtype epithelioid inflammatory myofibroblastic sarcoma (EIMS) are rare soft‐tissue tumors. As about 50% of IMT and 100% of EIMS contain activating rearrangements of the anaplastic lymphoma kinase ( ALK ) gene, targeted kinase inhibition of ALK by compounds such as crizotinib is a potential treatment option. We performed a literature review and analyzed a total of 30 patients with IMT/EIMS treated with crizotinib. A total of 12 patients achieved complete or partial remission. As preliminary data are promising, a prospective study evaluating crizotinib treatment in patients with unresectable/multifocal ALK + IMT/EIMS is warranted.